Effect of soy lecithin concentration on physiochemical properties and rehydration behavior of egg white protein powder: Role of dry and wet mixing. (September 2022) - Zhang, Ting; Yang, Yi; Zhang, Min; Jiang, Hongyu; Yan, Zhaohui; Liu, Jingbo; Liu, Xuanting
Abstract: The application of egg white protein powder (EWPP) was restricted by rehydration behaviour in food industry. In this study, the effects of dry mixing (DM) and wet mixing (WM) and soy lecithin (SL) concentration on the physiochemical and rehydration properties of EWPP were evaluated. The dispersibility and wettability of EWPP increased with increasing SL concentration, and the shortest dispersion time of the WM samples (37.5 ± 3.78 s) was lower than that of the DM samples (72.83 ± 11.57 s). Additionally, the higher net negative charge and smaller particle size of the WM samples helped explain their faster rehydration. The increase in free sulfhydryl groups and surface hydrophobicity in both samples suggested that SL promoted the unfolding of the egg white protein (EWP) secondary structure. Three-dimensional fluorescence spectrum and molecular docking analysis further demonstrated the formation of SL-EWP complexes. Overall, our research provides a new strategy for preparing instant EWPP. Highlights: SL-EWPP formation mechanism revealed by 3D fluorescence and molecular docking. Higher SL concentration enhanced EWPP rehydration, providing irregular particles. The dispersibility of WM sample was 2.79 times higher than that of control sample. EWP formed complexes with SL through hydrophobic and electrostatic interaction. EWPP rehydration properties were closely related to double electron layer structures.